Strategies for Strengthening the Purun Handicraft Creative Industry in Banjarbaru City South Kalimantan - Hesty Heryani; Agung Cahyo Legowo; Indra Prapto Nugroho (Conference Series, 2020)
Some research and development results that have been funded, the largest portion is Technology Readiness Level of 3-5. Very few researchers entered in 6,7, or 8 levels. In effort to bridge the results of research and implementation in society, the technology transfer program needs a strategy to strengthen human resources in the creative industry, especially purun crafts. The application of the Analytic Network Process method in selecting strategies was based on weighting of each criterion and alternative. The results of analysis gave priority weights for product performance and market performance sub-criteria which affect the choice of strategy, namely motive and product type sub-criteria of 0.48715, while customer satisfaction was 0.42224. In the alternative cluster, there were two strategies that became the best priority, namely development of creative products of 0.44857 and strengthening of purun handicraft brands in the Galoeh Bandjar and Al-Firdaus groups of 0.28947. Strategies to strengthen human resources in terms of creative product development and brand strengthening were done through education, training, and coaching based on the principles of Competitive Advantage.